Endoscopic Evacuation of Basal Ganglia Hemorrhage via Keyhole Approach Using an Adjustable Cannula in Comparison with Craniotomy. (18th May 2014) - Zhang, Heng-Zhu; Li, Yu-Ping; Yan, Zheng-cun; Wang, Xing-dong; She, Lei; Wang, Xiao-dong; Dong, Lun
Abstract : Neuroendoscopic (NE) surgery as a minimal invasive treatment for basal ganglia hemorrhage is a promising approach. The present study aims to evaluate the efficacy and safety of NE approach using an adjustable cannula to treat basal ganglia hemorrhage. In this study, we analysed the clinical and radiographic outcomes between NE group (21 cases) and craniotomy group (30 cases). The results indicated that NE surgery might be an effective and safe approach for basal ganglia haemorrhage, and it is also suggested that NE approach may improve good functional recovery. However, NE approach only suits the selected patient, and the usefulness of NE approach needs further randomized controlled trials (RCTs) to evaluate.